2005
DOI: 10.1128/aem.71.12.7819-7830.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Coastal Subsurface Sediments: a Cultivation Approach Using Various Electron Acceptors and Substrate Gradients

Abstract: Microbial communities in coastal subsurface sediments are scarcely investigated and have escaped attention so far. But since they are likely to play an important role in biogeochemical cycles, knowledge of their composition and ecological adaptations is important. Microbial communities in tidal sediments were investigated along the geochemical gradients from the surface down to a depth of 5.5 m. Most-probable-number (MPN) series were prepared with a variety of different carbon substrates, each at a low concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 61 publications
11
120
1
1
Order By: Relevance
“…Köster, personal communication, 2008). Microbial investigations by Köpke et al (2005) and Wilms et al (2006a) found significantly enhanced activity at the edges of the sulfate free, methanogenic zone. Though less pronounced, ongoing diagenesis is also visible at site NN2 in the sulfate profile.…”
Section: Study Area: Sedimentary and Geochemical Recordsmentioning
confidence: 99%
“…Köster, personal communication, 2008). Microbial investigations by Köpke et al (2005) and Wilms et al (2006a) found significantly enhanced activity at the edges of the sulfate free, methanogenic zone. Though less pronounced, ongoing diagenesis is also visible at site NN2 in the sulfate profile.…”
Section: Study Area: Sedimentary and Geochemical Recordsmentioning
confidence: 99%
“…As sulfate reducers and methanogens can be easily detected by specific important genes, which either encode for the dissimilatory sulfate reductase or the methyl-coenzyme M reductase, the recent studies focused on these groups (Wilms et al, 2007). It is well known that the terminal oxidizers make only a minor part of the community, whereas the fermentative microorganisms are more abundant (Schink, 2002;Kö pke et al, 2005;Wilms et al, 2006b). Thus, owing to a lack of a fermentation important gene, the largest part of the community remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Böttcher et al, 2000;Llobet-Brossa et al, 2002;Billerbeck et al, 2006;Al-Raei et al, 2009;Jansen et al, 2009) as well as on deeper sediment layers down to 5 m below the seafloor (mbsf) (e.g. Köpke et al, 2005;Wilms et al, 2006b;Beck et al, 2008b;Gittel et al, 2008;Røy et al, 2008). In addition, biogeochemical and microbial processes were studied in the water column and on suspended particulate matter (e.g.…”
Section: Introductionmentioning
confidence: 99%